2013
DOI: 10.1136/gutjnl-2013-305266
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAHNF1A-AS1regulates proliferation and migration in oesophageal adenocarcinoma cells

Abstract: Objectives Long non-coding RNAs (IncRNA) have been shown to play important roles in the development and progression of cancer. However, functional IncRNAs and their downstream mechanisms are largely unknown in the molecular pathogenesis of oesophageal adenocarcinoma (EAC) and its progression. Design IncRNAs that are abnormally upregulated in EACs were identified by RNA-sequencing analysis, followed by quantitative RT-PCR (qRTPCR) validation using tissues from 25 EAC patients. Cell biological assays in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(164 citation statements)
references
References 51 publications
1
162
1
Order By: Relevance
“…Therefore, we sought to systematically characterize lncRNA dysregulation at different stages of Barrett's disease. Previously, only two lncRNAs (HNF1A-AS1 and AFAP-AS1) have been reported as upregulated in EAC (16,17). Although these were upregulated in EAC compared with NE, we observed no difference between EAC and NDBE/LGD (Supplementary Fig.…”
Section: Long Noncoding Rnas Show Characteristic Differential Expresscontrasting
confidence: 52%
See 1 more Smart Citation
“…Therefore, we sought to systematically characterize lncRNA dysregulation at different stages of Barrett's disease. Previously, only two lncRNAs (HNF1A-AS1 and AFAP-AS1) have been reported as upregulated in EAC (16,17). Although these were upregulated in EAC compared with NE, we observed no difference between EAC and NDBE/LGD (Supplementary Fig.…”
Section: Long Noncoding Rnas Show Characteristic Differential Expresscontrasting
confidence: 52%
“…Most microarray-based transcriptome analyses will for example miss a large proportion of long noncoding RNAs (lncRNAs), which are involved in almost all known cellular processes (10)(11)(12)(13)(14), and are important in cancer biology, as shown by the number of functional characterized lncRNAs involved in carcinogenesis (15). In EAC, only two lncRNAs have been reported (16,17), and no systematic approach identifying lncRNAs dysregulation at different stages of Barrett's disease and EAC development has been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the function of uc009yby.1 in renal cells was investigated using two siRNAs to inhibit uc009yby.1 expression, revealing that this lncRNA could enhance renal cell proliferation; this suggests that uc009yby.1 may be a novel therapeutic target for ccRCC. Numerous studies have indicated that certain lncRNAs have aberrant expression profiles in various kinds of tumors, such as gastric (15)(16)(17), colon (18,19), esophageal (20)(21)(22) and liver (23) cancers. Yu et al (12) recently reported on a class of lncRNAs that are aberrantly expressed in ccRCC cells, in which multiple lncRNAs were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…They further confirmed that HNF1A, the sense-cognate gene for HNF1A-AS1, was not an HNF1A-AS1 target. Mechanistic investigation via gene ontology enrichment analysis revealed that HNF1A-AS1 knockdown dysregulated the expression of genes involved in cell cycle regulation and affected the expression of a cancer-related lncRNA H19, suggesting that one lncRNA may influence the function of another lncRNA in EACs [47].…”
Section: Function Of Other Lncrnasmentioning
confidence: 99%